Role of Learning Approach in Determining Learning Outcome During Active and Passive Learning Sessions in Pharmacology - Ananthy, Vimala; Narayanan, Suresh; Asokan, Arthi (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: The objective of the study is to estimate the difference in knowledge gain between the students of varied learning approaches during didactic lectures and concept mapping lectures. Materials and Methods: The study participants included 118 secondyear medical undergraduate students. The learning approaches of the participants were assessed using the ASSIST questionnaire on a 5-point Likert-type scale. Two lectures in pharmacology subject were taken using the concept mapping technique and two lectures were taken in didactic format with an equal difficulty level. The students’ prior knowledge was assessed using 40 MCQ’s that were given 4 days before the commencement of the lectures with 10 MCQs from each topic. The same questions were given to the students 3 weeks after the completion of the each lecture. Results: The score improvement of the three categories of learners was significantly higher for concept mapping session when compared to the didactic lectures. There was no significant difference in the score improvement between the surface, strategic and deep learners in both didactic and concept mapping sessions. Conclusion: The learning approach did not influence the long-term knowledge retention following didactic and concept mapping sessions. Learners study strategy and the mode of assessment could play a role in determining the knowledge outcome.
Keywords: Learning approach; Deep learners; Surface learners; Strategic learners; Learning outcome